Geochemistry and detrital zircon geochronology of Khammam Schist Belt, Eastern Dharwar Craton: Implication for India – North China Craton –Antarctica connection in Paleo-Mesoproterozoic crustal assembly - Ab Majeed Ganaie; Kausik Satpathi; Sayonjyoti Beura; Pritam Nasipuri (Geosystems and Geoenvironment, 2023)
This communication reports the results of geochemical investigations and detrital zircon geochronology of metasediments of the Khammam Schist Belt that occur at the trijunction of the Eastern Dharwar Craton–Bastar Craton–Eastern Ghats Belt. Biotite (XMg = 0.46–0.52) and muscovite (Si atom per formula unit (apfu) of 11 O = 3.08–3.17) with alkali-feldspar constitute the mineralogy of studied samples. The Ti content in biotite yields a mean temperature of 652 °C (1σ = 10 °C), and biotite–muscovite pairs yield an average pressure of 0.46 GPa (1σ = 0.06 GPa). Fe-Ti oxides and zircon occur as accessory phases. The Al2O3 exhibits a positive correlation with K2O and TiO2, which implies that mica and biotite control the major element abundances of studied samples. These samples indicate negative Sr and positive Th anomalies in a Post Archean Australian Shale (PASS) normalised spider diagram. Also, these samples show a nearly horizontal trend with (La/Yb) PASS varying between 0.56 and 1.92 with a negative to slightly positive Eu anomaly (Eu/Eu* = 1.20, 1σ = 0.38). LA-ICPMS analysis of detrital zircon grains (number of analyses = 100 from two samples) yields 207Pb/206Pb ages range from 1500 to 2600 Ma. The zircons grains with weighted average ages between 2500 Ma, 2400 Ma, 2200 Ma, 2000 Ma, 1900 and 1800 Ma exhibit magmatic and high-temperature deformation features. The 1604 Ma old zircons exhibit homogeneous domains and overgrowths over older zircons, implying metamorphic origin. The Chemical Index of Alteration (CIA = 66 to 77), Chemical Index of Weathering (CIW = 73 to 95), and Plagioclase Index of Alteration (PIA = 81 to 91) values indicate moderate to intense weathering of the source area. Source and tectonic discrimination plots imply a felsic source and active tectonic setting. Accordingly, 1900–1800 Ma old magmatic zircons in the current samples constrain the maximum depositional age for the Khammam Schist Belt. Compared with the detrital zircon geochronology of the North China Craton and East Antarctica, the ...